Characterization of patients using warfarin in relation to functional health literacy and identification of associated factors (Revista Brasileira Multidisciplinar, 2025)
Low functional health literacy in patients on warfarin anticoagulation has been widely discussed in the literature. Objective: To identify the quality of oral anticoagulation over time and to analyze the association between this variable and functional health literacy. Prospective cohort study conducted in an anticoagulation clinic in Minas Gerais, at a high complexity hospital. The study included 81 patients, whose data were collected through direct consultation of medical records or by asking questions during the waiting period for appointments. The quality of oral anticoagulation was assessed at 6, 9, 12, 15, and 18 months after the start of the study, with analyses of the association between this variable and functional health literacy at different time points. The quality of oral anticoagulation was identified by calculating the Therapeutic Time Range (TTR), with good quality defined as TTR values >59%. Inadequate control of oral anticoagulation was observed, with only 20% of patients showing persistent improvement in TTR values over the study period. No statistically significant association was found at different measurement times between TTR and functional health literacy. There was no direct association between the quality of oral anticoagulation and functional health literacy. However, the low incidence of persistence in anticoagulation quality among patients with low literacy suggests the need for specific educational interventions for this subgroup of patients.
Keywords: Health Literacy; Anticoagulants; Warfarin; Drug Utilization